O'Corry-Crowe et al - Biology Letters - Supplementary Tables from Genetic profiling links changing sea-ice to shifting beluga whale migration patterns - Greg O'Corry-Crowe; Andrew R. Mahoney; Robert Suydam; Lori Quakenbush; Alex Whiting; Lloyd Lowry; Lois Harwood (2016)
Genetic profiling links changing sea ice to shifting beluga whale migration patterns - Tables SM1 and SM2